Determining the Thermal Efficiency of Firing a Cross Draft Kiln using Methane and Liquefied Petroleum Gas - Ezra Abubakar; Kawahya Pastor Daniel; Iyam Gordy Anthony; Titikus Japheth Ibrahim (Program Pascasarjana Universitas Sriwijaya, 2022)
Thermal efficiency in the ceramic firing process is crucial to reducing energy consumption, emissions of gaseous pollutants and the cost of production. This study, reports on the determination of thermal efficiencies of a traditional 3m x 28m x 2.7m cross draft kiln using the heat balance approach. Results of the study showed thermal efficiencies of 46.4% and 1.9% for methane and liquefied petroleum gas kiln to 1, 200OC at ambient temperature of 26OC. Findings from the study also showed that only 2.1%, and 32.3% of the thermal energy inputs from methane, and liquefied petroleum gas (LPG) were effectively utilized for the physio-chemical transformation of ceramic ware. Findings also revealed that thermal energy wastes, in the form of heat losses through radiation, and convection accounted for up to 280,1522.7 kcal/kg, and 102,338.592 kcal/kg for both methane, and LPG fired kilns respectively. Other sources of heat wastages identified included heat lost in the form of waste heat and combusted exhaust gas. It is hoped that findings from this study, will aid in addressing the gross thermal inefficiency of the traditional cross draft kiln. Keywords: Ceramic, Firing, Greenhouse gas, Methane, Thermal efficiency.